Constraining kinematic rotation axes in high-strain zones: A potential microstructural method - Reddy, Steven; Buchan, Craig (Geological Society, 2005)
The correct determination of the kinematic rotation axis (vorticity) in high-strain zones is essential to the study of the tectonic evolution of the Earth's crust. Commonly the shear direction in high-strain zones is assumed to be parallel to mineral stretching lineations, that indicate the orientation of maximum finite stretch. However, during general shear deformation, where maximum finite stretch may lie oblique to the shear direction, the use of mineral stretching lineations to constrain shear directions may be invalid. In these situations, constraining the kinematic rotation axis of the deformation may be difficult. Electron backscatter diffraction data from calcite deformed in the high-strain Gressoney Shear Zone of the Western Alps, demonstrates a strong geometrical coincidence amongst the bulk macroscopic kinematic rotation axes, the orientation of misorientation axes associated with low-angle boundaries at the intergrain scale and rotation axes associated with crystallographic dispersion at the intragrain scale. These data suggest a geometric control of the kinematic framework of the high strain zone on the activity of crystal slip systems in calcite. It is proposed that this relationship can be exploited as a new tool to determine the orientation of bulk kinematic rotation axes in high-strain zones independent of mineral stretching lineations. Application of the approach could lead to a significant advance in our understanding of natural general shear deformation.